Web Intelligence and Intelligent Agents - Usmani, Zeeshan-Ul-Hassan (IntechOpen, 2010)
This book presents a unique and diversified collection of research work ranging from controlling the activities in virtual world to optimization of productivity in games, from collaborative recommendations to populate an open computational environment with autonomous hypothetical reasoning, and from dynamic health portal to measuring information quality, correctness, and readability from the web.